Assessment of the Influence of Municipal Economy Infrastructure on the Quality of Life of the Population - Ufimtseva, Evgeniya V.; Volchkova, Irina V.; Podoprigora, Yulia V.; Danilova, Maria N.; Shadeyko, Nikolay R.; Seliverstov, Alexey A. (International Review of Management and Marketing, 2016)
The aim of this study is to evaluate the effect of the development level of urban infrastructure on the quality of life of the population of the municipality. The study proposed an evaluation system formed on the basis of socio-economic indicators that characterize the quality of life. The relationship between quality of life and level of development of certain types of municipal services infrastructure is revealed. The paper concludes that the dependence models of the quality of life and types of municipal services infrastructure show that on average the quality of life is by 90% depends on the level of development of social, productive and household infrastructure. Keywords: municipal infrastructure, correlation analysis, municipal economy, urban development JEL Classifications: H41, R23, R31